1987
DOI: 10.1093/nar/15.4.1459
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific expression of the human alpha-1-antitrypsin gene in transgenic mice

Abstract: Normal and mutant human alpha-1-antitrypsin genes were cloned from a PiMZ heterozygous individual. Nucleotide sequence comparison demonstrated a T to C transition in exon III and an G to A transition in exon V of the PiZ gene. A 14.4 kb DNA fragment containing the entire PiM gene plus 2 kb of 5' and 3' flanking genomic DNA sequences was introduced into the germ line of mice and five F0 transgenic lines were established. Transgenic F1 progeny from F0 parents exhibited high levels of human alpha-1-antitrypsin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…Although sexual dimorphism of prorenin levels has been detected in some strains of rats (32), the extent of sexual dimorphism in transgene expression in our study was unexpected because endogenous ␣ 1-antitrypsin expression is only severalfold higher in male rats than in females (33). Furthermore, RNase analysis showed that transgene mRNA level in Prorenin, PRA (plasma renin activity), and angiotensinogen measured in ng of angiotensin I/ml/h, * P Ͻ 0.001 vs. nontransgenic rats.…”
Section: Discussionmentioning
confidence: 54%
“…Although sexual dimorphism of prorenin levels has been detected in some strains of rats (32), the extent of sexual dimorphism in transgene expression in our study was unexpected because endogenous ␣ 1-antitrypsin expression is only severalfold higher in male rats than in females (33). Furthermore, RNase analysis showed that transgene mRNA level in Prorenin, PRA (plasma renin activity), and angiotensinogen measured in ng of angiotensin I/ml/h, * P Ͻ 0.001 vs. nontransgenic rats.…”
Section: Discussionmentioning
confidence: 54%
“…Transgenic PiZ mice express human AAT-Z from its native promoter elements (12). Tissue distribution of transgene expression recapitulates that in humans (13).…”
Section: Resultsmentioning
confidence: 67%
“…Although α1-antitrypsin variant PI Z misfolds following biosynthesis (Elliott et al, 1996) in response to a E342K substitution (Sifers et al, 1987), it fails to induce the UPR in any of the cell lines in which it has been expressed (Hidvegi et al, 2005;Lawless et al, 2004), including HEK293 (Cabral et al, 2002). Because variant PI Z is subject to proteasomal degradation in transfected HEK293 cells (Cabral et al, 2002;Wu et al, 2003) in the next set of experiments it served as a reporter protein to measure changes in the efficiency of ERAD under basal conditions and in response to the experimental overexpression, or knockdown, of ERManI or EDEM1.…”
Section: Knockdown Of Ermani But Not Edem1 Diminishes Basal Eradmentioning
confidence: 99%